2019
DOI: 10.3389/fneur.2019.00880
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Outcome and Its Prognostic Predictors After Hemispherotomy in Children With Refractory Epilepsy in a Chinese Pediatric Epileptic Center

Abstract: Object: To explore the post-hemispherotomy seizure outcome and its prognostic predictors in children with refractory epilepsy. Methods: We reviewed 83 consecutive child patients with refractory epilepsy who underwent a hemispherectomy from June 2014 to January 2017 at our Pediatric Epilepsy Center. Demographic, clinical, EEG, neuroimaging, and surgical data were collected. Seizure outcome data were collected via outpatient clinics as well as telephone visits and were graded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…After exclusion of 111 studies (42 did not meet the inclusion criteria, 35 included overlapping populations, and 34 had insufficient data), a total of 25 studies met the inclusion criteria and were included in our study. 6,8,11,16,17,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] All 25 studies were retrospective consecutive case series and published between 2000 and 2019, with the cumulative studied period ranging from 1990 to 2017. Sev-enteen studies reported on LPH, 7 reported on VPH, and 1 included both techniques (Table 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After exclusion of 111 studies (42 did not meet the inclusion criteria, 35 included overlapping populations, and 34 had insufficient data), a total of 25 studies met the inclusion criteria and were included in our study. 6,8,11,16,17,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] All 25 studies were retrospective consecutive case series and published between 2000 and 2019, with the cumulative studied period ranging from 1990 to 2017. Sev-enteen studies reported on LPH, 7 reported on VPH, and 1 included both techniques (Table 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The epilepsy type and v-EEG also appeared to have varying degrees of predictive value for surgical outcomes in the present study, as in some previous studies. 19 Sex, age at first seizure, age at surgery, and seizure duration had no additional predictive value.…”
Section: Discussionmentioning
confidence: 89%
“…Surgery should be determined by comprehensive symptomatology, v-EEG, and PET/CT findings. 19 Multiple studies have shown that patients with unilateral focal PET abnormality might have better post-surgical seizure outcomes, while non-specific or bilateral FDG hypometabolism tends to predict poor seizure outcomes. 19,20 The present data showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their series, 30/84 (35.7%) children had dysplastic pathology, a similar portion to the current systematic review (40.8%). Interestingly, one large class 3 study of 84 patients undergoing PIH did not observe any significant difference in Engel outcome between developmental and acquired pathology groups (86.9%, 83.3%, respectively) [28]. These insights suggest surgeon preference and experience may be more important than technique differences for patients with developmental pathology.…”
Section: Discussionmentioning
confidence: 99%